1999
DOI: 10.1177/0146167299025001008
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentrism, Social Identification, and Discrimination

Abstract: In line with social identity theory (SIT), minimal group paradigm (MGP) studies have shown that high in-group identifiers discriminate more than low in-group identifiers. But why do some people identify more to their ad hoc group in the MGP? One week prior to a MGP study, 121 undergraduates completed scales assessing their ethnocentrism, authoritarianism, and personal need for structure. In Phase 2, the same participants took part in a MGP study in which us-them categorization was either assigned randomly or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 44 publications
5
148
0
6
Order By: Relevance
“…The more individuals identify with a group, the more they will differentiate themselves from other groups leading to stereotypical perceptions of others (Perreault & Bourhis, 1999). This is the theoretical point of departure for the present thesis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The more individuals identify with a group, the more they will differentiate themselves from other groups leading to stereotypical perceptions of others (Perreault & Bourhis, 1999). This is the theoretical point of departure for the present thesis.…”
Section: Discussionmentioning
confidence: 85%
“…Ingroup identification in turn leads to ingroup favoritism; positive affect towards the ingroup which is automatically activated (Brewer, 2007a). A positive ingroup image is achieved by systematically altering perceptions of reality in favor of the own group (Allport, 1954;Brewer, 2007a;Perreault & Bourhis, 1999;Tajfel et al, 1971).…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Research also has shown that ethnocentrism and social identity are central to ethnic prejudice [11]. Therefore, it is crucial to include this variable in studying people's attitude toward ethnic jokes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies show that, when experimentally manipulated, it is high (rather than low) levels of collective identity, which lead to greater ingroup bias [5][6][7][8]. The correlational evidence, which constitutes the vast majority of the evidence in this area is, however, much more inconsistent and contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Several analyses show a clear link between collective identity and intergroup discrimination [8,[10][11][12][13][14]. Other work reports little evidence of such relationships [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%